Pirate - Bell, Ted. (New York : Pocket Star Books, 2006)
When a ruthless descendant of Napoleon rises to power in Paris, he forms an alliance with the cold-blooded Mandarins, developing a plan that will start a nuclear showdown with the rest of the world, and Alex Hawke sets out to stop the evil plot before it destroys the world.
Adult
Adult
Keywords: Intelligence officers -- Fiction; Pirates -- Fiction; Terrorism -- Prevention -- Fiction; Adventure fiction; Intelligence officers -- Fiction; Pirates -- Fiction; Terrorism -- Prevention -- Fiction; Adventure fiction